1999
DOI: 10.1042/cs19980238
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in 1-day-old infants born at 4330 m altitude

Abstract: In fetuses and newborn infants heart rate variability changes in conditions of acute and chronic hypoxia; we therefore asked whether heart rate variability of infants born at high altitude differed from that of low-altitude infants. Short-term recordings (4-5 min) of inter-beat intervals were obtained in 19 infants in Lima (50 m altitude) and in 15 infants in Cerro de Pasco (4330 m, barometric pressure approximately 450 mmHg, inspired oxygen pressure approximately 94 mmHg) during quiet rest in warm conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The quantification of variability from a time series of IBI was based on five criteria commonly adopted in the time-domain analysis of IBI; 44,45 then, the results of these five criteria were lumped together into a 'variability index' (VI; Table 2). The first criterion was the coefficient of variation of all the IBI, computed as the percent ratio of standard deviation (the square root of the variance) and mean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of variability from a time series of IBI was based on five criteria commonly adopted in the time-domain analysis of IBI; 44,45 then, the results of these five criteria were lumped together into a 'variability index' (VI; Table 2). The first criterion was the coefficient of variation of all the IBI, computed as the percent ratio of standard deviation (the square root of the variance) and mean.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In hypoxia, the short- and long-term prognostic values of HRV and BRV are unknown because of the ethical and practical difficulties encountered by studies on human infants. Data on infants born at high altitude could be informative 45 but need to consider the responses of the pregnant mother to hypobaric hypoxia. The current study has shown that the avian embryo can be an excellent model for the investigations of HRV and BRV in the transition from prenatal to postnatal life and their responses to hypoxia, and could offer a valuable experimental approach to assess the role of BRV and HRV as predictors of outcome.…”
Section: Discussionmentioning
confidence: 99%